2022
DOI: 10.48550/arxiv.2205.06163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaussian Whittle-Matérn fields on metric graphs

Abstract: We define a new class of Gaussian processes on compact metric graphs such as street or river networks. The proposed models, the Whittle-Matérn fields, are defined via a fractional stochastic partial differential equation on the compact metric graph and are a natural extension of Gaussian fields with Matérn covariance functions on Euclidean domains to the non-Euclidean metric graph setting. Existence of the processes, as well as their sample path regularity properties are derived. The model class in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Future work information about their position. To enable network-wide modeling that explicitly take space into account, we can model the processes spatially on a grid over the urban layout, or even directly over the bus network graph as recently proposed by Bolin et al (2022).…”
Section: Future Workmentioning
confidence: 99%
“…Future work information about their position. To enable network-wide modeling that explicitly take space into account, we can model the processes spatially on a grid over the urban layout, or even directly over the bus network graph as recently proposed by Bolin et al (2022).…”
Section: Future Workmentioning
confidence: 99%
“…proposed extrinsic framework for GP modeling on manifolds, which relies on embedding of the manifold into a Euclidean space and then constructing extrinsic kernels for GPs on their images. Dunson et al (2020) , Borovitskiy et al (2021) and Bolin et al (2022) focused on developing GPs on graphs and metric graphs formed by data observed on the manifold.…”
Section: Introductionmentioning
confidence: 99%